Proteomic analysis in wild type and cisplatin resistant yeast strain of saccharomyces cerevisiae - Burgos-Molina, Antonio Manuel; Gil-Carmona, Luisa; Ruiz-Gómez, Miguel José (My University, 2019)
Research carried out in oncology has allowed the identification and characterization of molecular markers of resistance to antineoplastic drugs. It supposes a great advance and allows the administration of customized chemotherapies to patients. The aim of this work is to carry out a proteomic analysis in the wild type strain and cisplatin resistant strain of Saccharomyces cerevisiae in order to look for possible markers of resistance, as well as the mechanisms involved.
Keywords: Radiología; Cistiplatin resistant; Biomarkers; Proteomic analysis